DESAIN ‘’KACA’’ UNTUK MEMBANTU PEMAHAMAN PESERTA DIDIK TENTANG KONSEP PECAHAN BIASA: “KACA” DESIGN TO HELP STUDENTS UNDERSTAND THE CONCEPT OF SIMPLE FRACTIONS - annisa nurul puteri; della pratiwi; eni tri sundari; marissa dewi meilani; sabna laila fitri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
Proper fractions are one of the important topics in elementary school mathematics education. A strong understanding of the concept of proper fractions is very important for learners, as this concept serves as the foundation for understanding various advanced mathematical operations, such as addition, subtraction, multiplication, and division of fractions. This research aims to determine the design of fraction card learning media on the topic of simple fractions and to measure how far this media can help in understanding the concept of fractions. This research uses Research and Development (R&D) aimed at helping students understand the concept of fractions. The subjects of this research are several educators from Sukadana Timur Public Elementary School. The data analysis technique used is a questionnaire as a design feasibility test. The results of the research on the